Na(+)- and Cl(–)-coupled active transport of nitric oxide synthase inhibitors via amino acid transport system B(0,+) - Hatanaka, Takahiro (American Society for Clinical Investigation, 2001)
Nitric oxide synthase (NOS) inhibitors have therapeutic potential in the management of numerous conditions in which NO overproduction plays a critical role. Identification of transport systems in the intestine that can mediate the uptake of NOS inhibitors is important to assess the oral bioavailability and therapeutic efficacy of these potential drugs. Here, we have cloned the Na(+)- and Cl(–)-coupled amino acid transport system B(0,+) (ATB(0,+)) from the mouse colon and investigated its ability to transport NOS inhibitors. When expressed in mammalian cells, ATB(0,+) can transport a variety of zwitterionic and cationic amino acids in a Na(+)- and Cl(–)-coupled manner. Each of the NOS inhibitors tested compete with glycine for uptake through this transport system. Furthermore, using a tritiated analog of the NOS inhibitor N(G)-nitro-L-arginine, we showed that Na(+)- and Cl(–)-coupled transport occurs via ATB(0,+). We then studied transport of a wide variety of NOS inhibitors in Xenopus laevis oocytes expressing the cloned ATB(0,+) and found that ATB(0,+) can transport a broad range of zwitterionic or cationic NOS inhibitors. These data represent the first identification of an ion gradient–driven transport system for NOS inhibitors in the intestinal tract.